2008
DOI: 10.1007/s10765-007-0320-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cobalt–Carbon and Palladium–Carbon Eutectic Point Cells for Thermocouple Calibration

Abstract: Two cobalt-carbon (Co-C) eutectic point (1,324 • C) cells and one palladium-carbon (Pd-C) eutectic point (1,492 • C) cell were constructed for thermocouple calibration. The lengths of the Co-C and Pd-C cells were 297 mm, 140 mm, and 140 mm, respectively. The melting and freezing plateaux at the Co-C and Pd-C eutectic points were observed using Pt/Pd thermocouples. The repeatability of the plateau, the effect of the surrounding temperature, and the temperature profile in the cell were measured, and the heat flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 7 publications
(8 reference statements)
1
28
0
Order By: Relevance
“…CoC-L-2 and CoC-NMIJ were designed and constructed at LNE-Cnam and NMIJ, respectively. A schematic diagram and construction procedure of CoC-L-2 are described in [9], while those of CoC-NMIJ are described in [5] as the "Co-C (Cell-B)" cell. Crucible pieces of CoC-L-2 were made of high-purity graphite (grade R6710) supplied by SGL Carbon and had an ash content of less than 5 ppm.…”
Section: Co-c Eutectic-point Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…CoC-L-2 and CoC-NMIJ were designed and constructed at LNE-Cnam and NMIJ, respectively. A schematic diagram and construction procedure of CoC-L-2 are described in [9], while those of CoC-NMIJ are described in [5] as the "Co-C (Cell-B)" cell. Crucible pieces of CoC-L-2 were made of high-purity graphite (grade R6710) supplied by SGL Carbon and had an ash content of less than 5 ppm.…”
Section: Co-c Eutectic-point Cellsmentioning
confidence: 99%
“…Schematic diagrams of PdC-LNE and PdC-NMIJ are described in [6] and [5], respectively. The purity and supplier of crucibles Palladium powder of 99.998+ % nominal purity (metals basis) was supplied by Alfa Aesar.…”
Section: Pd-c Eutectic-point Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The melting points of the metal-carbon eutectic alloys Co-C (1324 • C) and Pd-C (1492 • C) are at particularly convenient temperatures for the calibration of thermocouples [1][2][3][4][5][6][7], being located between the freezing points of the conventionally used Cu (1085 • C) and Pd (1553 • C) fixed points. However, one pressing problem is still the assignment of an agreed temperature to these eutectic fixed points.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been carried out to investigate the use of eutectics for thermocouple calibration [3,4,[5][6][7][8][9][10][11][12]. Edler et al [6] used four Pt/Pd thermocouples calibrated at two national measurement institutes (NMIs) (PTB and Inmetro) to obtain 1323.81°C ± 0.27 C (k = 2) for the melting temperature of Co-C. Sadli et al [13] compiled temperatures from many radiation thermometry studies and suggested a temperature of 1324.0°C ± 0.6 C (k = 2) for Co-C.…”
Section: Introductionmentioning
confidence: 99%